2014
DOI: 10.1208/s12248-014-9645-0
|View full text |Cite
|
Sign up to set email alerts
|

Population Pharmacokinetic/Pharmacodynamic Modeling of Guanfacine Effects on QTc and Heart Rate in Pediatric Patients

Abstract: Abstract. Using a previously developed population pharmacokinetic model, an exposure-response (ER) model was successfully developed to describe guanfacine plasma concentrations and changes in heart rate (HR) and the QT interval. Guanfacine exposure was associated with small decreases in HR and a small prolongation of the population-corrected QT (QTcP) interval. Based on the final ER model for effect of guanfacine on HR, the estimated population typical decrease in HR would be 2.3% (2.1-2.7%) of the baseline ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
(12 reference statements)
2
2
0
Order By: Relevance
“…To our knowledge, comprehensive baseline heart rate models using circadian rhythm in adults are not currently available, although a 24-hour circadian rhythm model for heart rate in pediatrics has been reported. 21 The time course of systolic and diastolic BP in the current analyses was described using a single 24-hour circadian rhythm, consistent with that described by Conrado et al 22 Other time-related effects were also observed in the baseline measures, which reached a steady state within 2-3 days. These time-related drifts cannot be clearly explained and could be attributed to the interday and intraday performances of the electrocardiogram tracings.…”
Section: Placebo Models For Cardiovascular Safety Variablessupporting
confidence: 88%
See 1 more Smart Citation
“…To our knowledge, comprehensive baseline heart rate models using circadian rhythm in adults are not currently available, although a 24-hour circadian rhythm model for heart rate in pediatrics has been reported. 21 The time course of systolic and diastolic BP in the current analyses was described using a single 24-hour circadian rhythm, consistent with that described by Conrado et al 22 Other time-related effects were also observed in the baseline measures, which reached a steady state within 2-3 days. These time-related drifts cannot be clearly explained and could be attributed to the interday and intraday performances of the electrocardiogram tracings.…”
Section: Placebo Models For Cardiovascular Safety Variablessupporting
confidence: 88%
“…Consistent with our analyses, Piotrovsky has previously described the QT interval time course using three cosine (oscillation) functions. To our knowledge, comprehensive baseline heart rate models using circadian rhythm in adults are not currently available, although a 24‐hour circadian rhythm model for heart rate in pediatrics has been reported . The time course of systolic and diastolic BP in the current analyses was described using a single 24‐hour circadian rhythm, consistent with that described by Conrado et al .…”
Section: Discussionsupporting
confidence: 75%
“…Guanfacine, a centrally acting α2A adrenergic receptor agonist, is an agent used for ADHD and is a well‐known QT prolonging drug that acts in a dose‐dependent manner. 25 Although a number of reports about QT prolongation with guanfacine have been mentioned in the JADER database, it is used mostly in young patients, and reports of life‐threatening ventricular arrhythmias are rare in the young age groups in the JADER database. There are few reports of TdP or other ventricular arrhythmias with guanfacine.…”
Section: Discussionmentioning
confidence: 99%
“…This mixed-effects method or the inclusion of DDRR may be helpful, especially in cases in which standard corrections for QTc values do not consistently correct across all ranges of HR, particularly for cardiovascular drugs. [11][12][13] Conclusion Linear regression of QTc versus the baseline-adjusted, time-matched, placebo-adjusted RR (DDRR) provided the best correction method of QTc for HR, particularly at the highest values. The linear mixed-effects model used to describe the relationship between olmesartan concentrations and DDQTc included DDRR as a covariate.…”
Section: Discussionmentioning
confidence: 99%